FORMULASI COOKIES DENGAN FORTIFIKASI TEPUNG TEMPE DENGAN PENAMBAHAN ROSELA (Hibiscus sabdariffa L.) - Seveline Seveline; Nofi Diana; Moh. Taufik (Universitas Trilogi, 2019)
Cookies are a type of pastry that is consumed by many people from all of aged. Cookies can be consumed as a practical and healthy alternative food. This research aims to formulate cookies combined from wheat flour and tempeh flour with addition of roselle. The use of tempeh flour in making cookies can increase protein levels because the protein content of tempeh flour is higher than in wheat flour. In addition, the important ingredients contained in the roselle petals are anthocyanin pigments that form flavonoids that act as antioxidants. The results of this study obtained 37.00% yield of tempeh flour and moisture content of 7.36%, ash content of 2.6%, protein content of 45.59%, fat content of 24.04 % and carbohydrate content of 0.134%. Roselle produced has yield of 80.5% and has a moisture content of 7.44 %, ash content of 6.28%, protein content of 6.29%, fat content of 1% and carbohydrate levels of 78.36%. Based on the result of hedonic test, formulas F1 was selected as the best formula. Products of tempeh flour cookies and roselle powder have a yield of 72 - 85.09%. The results of physicochemical analysis of F1 cookies obtained 2.40% ash content, 7.26% protein content, 29.62% fat content, 68.60% antioxidant activity EC50 µg/ml, 206.785